2021
DOI: 10.1590/0004-282x-anp-2020-0154
|View full text |Cite
|
Sign up to set email alerts
|

Clinical-epidemiological characteristics associated with discharge outcomes and seasonality among surviving patients with Guillain-Barré syndrome in a national third-level hospital, Lima, Peru

Abstract: Background: Guillain-Barré syndrome (GBS) is an autoimmune disease that affects the peripheral nervous system. Severe motor deficit (SMD), respiratory impairment, cranial nerve involvement and autonomic dysfunction are associated with a poor prognosis. Objective: To investigate the association between the clinical-epidemiological characteristics and the discharge results among Peruvian patients with GBS. Methods: We carried out a retrospective observational study on patients with GBS who survived until disch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…Our study observed that the most prevalent immune trigger was, also, gastroenteritis (30.3%) followed by upper airways infection (15.2%) and vaccination (12.1%). Furthermore, these results bring us closer to what happens in Peru, where gastroenteritis is also the most common immune trigger for GBS (30.4%) 22 .…”
Section: Discussionsupporting
confidence: 52%
“…Our study observed that the most prevalent immune trigger was, also, gastroenteritis (30.3%) followed by upper airways infection (15.2%) and vaccination (12.1%). Furthermore, these results bring us closer to what happens in Peru, where gastroenteritis is also the most common immune trigger for GBS (30.4%) 22 .…”
Section: Discussionsupporting
confidence: 52%